ANALISA SISTEM INFORMASI PERSURATAN DAN DISPOSISI ELEKTRONIK MENGGUNAKAN METODE SYSTEM USABILITY SCALE - Mitha Rachmani; Eka Rini Yulia (Program Studi DIII Sistem Informasi - Universitas Muhammadiyah Metro, 2026)
Digital transformation within the Attorney General’s Office of the Republic of Indonesia has led to the implementation of the Electronic Correspondence and Disposition Information System (SIPEDE) as an integrated platform to improve the effectiveness and efficiency of administrative processes. Nevertheless, the success of a system implementation is not solely determined by its technological sophistication, but also by the level of usability experienced by its users. Accordingly, this study aims to measure and analyze the usability level of SIPEDE using the System Usability Scale (SUS) method. This research employed a descriptive quantitative approach involving 100 respondents who are active users of the system. The data were collected through the standard SUS questionnaire consisting of 10 statements measured using a Likert scale. Subsequently, the responses were calculated in accordance with the established SUS scoring procedure to obtain a final score ranging from 0 to 100. The findings reveal that SIPEDE achieved a SUS score of 69.8. Based on standard SUS interpretation, this score falls within the Marginal High category, categorized as Acceptable within the Acceptability Range, and corresponds to Grade C on the Grade Scale. These results indicate that the system is generally usable and accepted by users; however, further improvements are necessary to enhance overall user experience and system performance.